Istihsan Concept and its Application in Determining the Legal Status of Halal Tourism - Widodo, Prima Ariyo (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Linguistically speaking, Istihsan is the masdar version of the word Istahsan - Yastahsin - Istihsana, which denotes thinking about, pondering the existence of, or seeking for something better to follow. The definition of "shara" according to Abdul Wahhab Khallaf, Istihsan, is "Transferring a mujtahid from the law kulli (generic) to the law of exceptions due to the evidence supporting it, or from qiyas prison (clear) to qiyas khafi (vague). The author of this study restricts it to the use of the concept of Istihsan in determining the legal status of halal tourism. In Islamic law, the idea of istihsan is an ijtihad technique that permits a mujtahid, or Islamic jurist, to base the law on morality or fairness. Istihsan can be used to evaluate the moral and just components of tourism-related activities in order to establish the legal status of halal travel. By guaranteeing that tourist operations adhere to sharia principles and must be founded on maslahah mursalah for each user or customer, this notion can serve as the foundation for establishing the legal status of halal tourism. The legal status of halal tourism can thus be ascertained by using the notion of istihsan and the tenets of sharia economic law, taking into account elements of fairness, morality, and compliance with sharia principles.